2008
DOI: 10.1159/000116774
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Brain-Gut Axis in the Pathophysiology of Crohn’s Disease

Abstract: Studies on the interaction between the central nervous system and the gastrointestinal system have shed light on the neurobiological response to stress via the hypothalamic-pituitary-adrenal and the hypothalamic-autonomic nervous system axes. These findings support a role of psychological and environmental factors in the course of gastrointestinal disorders and their influence on the neuroendocrine regulation of the immune system. Crohn’s disease (CD) is a chronic inflammatory condition of the gastrointestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 108 publications
0
32
0
3
Order By: Relevance
“…Inversely, it has been shown that the brain and spinal cord may modulate inflammation in IBD. 15,16 Neurological and other extraintestinal manifestations of IBD CD and UC are the two major types of IBD. Three main factors are thought to be involved in the development of chronic inflammation in IBD 17 : a reaction to a persistent intestinal infection; a defective mucosal barrier to luminal antigens; and a dysregulation of the immune response to ubiquitous antigens in a host with genetically determined susceptibility.…”
Section: Brain-gut Interactionsmentioning
confidence: 99%
“…Inversely, it has been shown that the brain and spinal cord may modulate inflammation in IBD. 15,16 Neurological and other extraintestinal manifestations of IBD CD and UC are the two major types of IBD. Three main factors are thought to be involved in the development of chronic inflammation in IBD 17 : a reaction to a persistent intestinal infection; a defective mucosal barrier to luminal antigens; and a dysregulation of the immune response to ubiquitous antigens in a host with genetically determined susceptibility.…”
Section: Brain-gut Interactionsmentioning
confidence: 99%
“…Stress may also have a role to play in modulating barrier function and aspects of the innate immune system in the intestine [110]. Catecholamines attenuate lipopolysaccharide-and other ligand-mediated responses in monocyte/macrophage populations in vitro [111,112] by inhibiting NF-κB-mediated transcription [113].…”
Section: Lifestyle Factors May Influence Intestinal Barrier and Innate mentioning
confidence: 99%
“…The modified Rankin scale (mRS) and the National Institutes of Health Stroke Scale (NIHSS) are among the most frequently used poststroke measures of functional outcome [10], despite their limitations [11]. Many neurological deficits are not captured by these scales; in particular, cognitive functions are not measured directly except for the language subtest in the NIHSS.…”
Section: Introductionmentioning
confidence: 99%